14 to 18-year-old Hungarian high-school students’ view of mathematicians appearing in the media - a case study - Lócska, Orsolya Dóra; Kovács, Zoltán (Teaching Mathematics and Computer Science, 2018)
One way to develop positive attitude toward STEM subjects that popular media, including movies and films can be engaged to promote more positive and inclusive STEM images. The movie Hidden numbers offers an opportunity to explore the representations of scholars, especially mathematicians within a biographical drama. Focusing on 5 characters, this article first discusses whether these characters fit into stereotypical scientist image or not. Secondly, we examine how high school students evaluate these characters. We argue that this movie is suitable to promote positive attitude toward STEM subjects.